Uniwersalny charakter myśli Jana Pawła II o człowieku i wychowaniu = The universal character of John Paul II`s reflections on man and education - Kobyłecka, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present paper has discussed some of Karol Wojtyła`s precious remarks derived from adequate anthropology conception as well as from his comments on the integral education of a human being in family and school environment, with a special regard to its spiritual, moral, social, national and cultural dimensions.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; wychowanie moralne - katolicyzm; moral education - Catholicism